Effect of a capsular tension ring on axial intraocular lens position. Issue 1 (January 2015) - Weber, Maria; Hirnschall, Nino; Rigal, Karl; Findl, Oliver
Abstract : Purpose : To assess the effect of a capsular tension ring (CTR) on the postoperative anterior chamber depth (ACD). Setting : Vienna Institute for Research in Ocular Surgery, Department of Ophthalmology, Hanusch Hospital, Vienna, Austria. Design : Prospective observer‐ and patient‐masked randomized trial. Methods : Bilateral small‐incision cataract surgery with implantation of a hydrophobic acrylic single‐piece intraocular lens (IOL) (Tecnis ZCB00) was performed using a standard technique. Each patient received a CTR in 1 eye (CTR group) and no CTR in the fellow eye (control group). The ACD was measured preoperatively with biometry (IOLMaster 500) and at 1 hour and 12 weeks postoperatively using partial coherence interferometry (ACMaster). The subjective refraction was assessed at 12 weeks. Results : Sixty eyes (30 patients) were included. Preoperatively, the mean axial length was 23.36 mm ± 1.55 (SD) (range 21.01 to 29.46 mm) in the CTR group and 23.37 ± 1.70 mm (range 21.14 to 28.84 mm) in the control group and the mean ACD was 3.06 ± 0.45 mm (range 2.25 to 4.16 mm) and 3.03 ± 0.47 mm (range 2.18 to 4.10 mm), respectively. The differences were not statistically significant ( P =.148 and P =.074, respectively). The mean postoperative ACD was 4.83 ± 0.46 mm (range 3.84 to 5.76 mm) in the CTR group and 4.81 ± 0.43 mm (range 3.67 to 5.65 mm) in the control group. The difference between the groups was not statistically significant ( P =.329). Conclusion : Implantation of a CTR had no significant influence on the postoperative axial IOL position. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.